Developing a Digital Management System for iOS Devices - Using an Agile Development Method - Söderbaum, Peter (My University, 2011)
The goal for every McDonald’s restaurant is to deliver quality, service and cleanliness to all customers at every visit. To succeed with this the restaurants depends very much on the shift managers responsible for the daily operations. The purpose of this master thesis project is to simplify the work of the shift managers by providing a digital management system. The goal is that the delivered system shall be able to handle the tasks that today’s system do in an easier way. It shall also add new functionality simplifying the work. If the work of the shift managers can be simplified their performance will increase. Better performing shift managers will generate better results at the restaurant. An agile development method was used to develop the digital management system. This method was based on the extreme programming method. Though this project was carried out by a single developer the extreme programming method had to be reworked to fit a single developer environment. The project resulted in a prototype that were tested at the restaurant during ordinary operations. Overall the results of the prototype were positive and a system like the one developed during this project will be able to help the restaurant to deliver better results. A digital management system is a viable option for a McDonald’s restaurant. The project shows that the possibilities of the digital management system exceeds today’s system by far. Further development will be made to the prototype to make it able to replace today’s system. Sammanfattning Alla McDonald’s restaurangers mål är att leverera kvalitet, service och renlighet till alla gäster vid varje besök. För att lyckas med detta förlitar sig restaurangerna mycket på skiftledarna som är ansvariga för den dagliga driften. Syftet med detta examensarbete är att förenkla arbetet för skiftledarna genom att utveckla ett digitalt verktyg för uppföljning av den dagliga driften. Målet är att det levererade systemet ska klara av de uppgifter som dagens system hanterar fast på ett enklare sätt. Det ska också addera nya funktioner som förenklar arbetet. Blir arbetsledarnas arbete enklare kommer de att prestera bättre. Skiftledare som presterar bättre kommer att generera bättre resultat på restaurangen. En agil systemutvecklingsmetod användes för att utveckla det digitala systemet. Metoden baserades på metoden extreme programming. Eftersom detta examensarbete utfördes av en ensam utvecklare behövde extreme programming metoden omarbetas för att passa ensamutveckling. Projektet resulterade i en prototyp som testades i den dagliga verksamheten. De övergripande resultaten var positiva och visar att ett system likt det som utvecklats under detta projekt kan hjälpa restaurangen att leverera ett bättre resultat. Slutsatsen är att ett digitalt system är en gångbar lösning för en McDonald’s restaurang. Projektet visar att möjligheterna för det digitala systemet är mycket större än de för dagens system. Prototypen kommer att utvecklas vidare för att kunna ersätta nuvarande system.
Keywords: Programvaruteknik; Software Engineering